Relationship Of Parity, Education And Sources Of Information With The Level Of Knowledge Of The Mother About The Provision Of Immunization Basis In Desa Barbaran Jae Kec. Panyabungan Barat Tahun 2019 - Helmi Wardah Nasution (Sean Institute, 2019)
Currently, almost one million children each year do not receive an immunization program. 2007 data shows that only 6 out of 10 children in Indonesia receive a complete immunization program. In fact, 9 out of 100 children do not get vaccinated at all. The percentage of children who received complete vaccination for DPT was only 66.7%. The immunization percentage for hepatitis B was 60.3%; for tuberculosis 85.4%, for Polio 73.5%, and for measles 76.4%. This type of research used an analytic study with a cross sectional design, which aims to explain the relationship between parity, education and sources of information with the level of mother's knowledge about the completeness of basic immunization. Data analysis was done by chi square test. The population in this study were all mothers who had babies aged 0-12 months in Barbaran jae village, kec. West Panyabungan as many as 31 people. The sample in this study was the entire population, namely mothers who have babies aged 0-12 months in Barbaran Jae Village, Kec. Panyabungan Barat as many as 31 people. The highest frequency distribution was found in sufficient knowledge, namely 17 respondents (54.8%), multipara parity, namely 19 respondents (61.3%), academic education/PT, namely 13 respondents (41.9%), and sources of information print media that is 17 respondents (54.8%). There was a correlation between parity (P = 0.045), education (P = 0.001), and sources of information (P = 0.026), with the mother's level of knowledge about the completeness of basic immunization in Barbaran Jae Village, Kec. West Connection.